Comparison of Energy and Frequency of Nanosecond Q-switched ND-YAG Laser and Chlorhexidine on Reducing the Number of Oral Streptococcus Mutans Isolates: In Vitro Study - Zakavi, Faramarz; Kazemi, Nazanin; Kaviani , Azita; Sabaeian, Mohammad; Hashemzadeh, Mohammad (Galen Medical Journal, 2025)
Background: Streptococcus mutans is a facultative anaerobic coccus that is a part of the oral flora of humans. chlorhexidine also has some side effects. Today, Nd: YAG lasers have become very popular in dentistry and are used for various types of treatment. Therefore, this study aims to compare the effects of Chlorhexidine 2% and nanosecond (Nd: YAG) laser in reducing the number of oral Streptococcus mutans bacteria in the oral cavity. Materials and Methods: An in vitro experimental design was conducted using S. mutans ATCC 35668 cultured on Mueller-Hinton agar. Bacterial suspensions were standardized to a half-McFarland turbidity and distributed in 96-well plates. The antimicrobial activity of 2% CHX was assessed via the well-diffusion method. Laser irradiation was applied at varying energies (10, 20, 30 mJ) and frequencies (5, 10 Hz). Bacterial counts and inhibition zone diameters were measured, and data were analyzed using two-way ANOVA followed by Tukey post hoc tests (α=0.05). Results: Bacterial counts decreased with increasing laser energy and frequency, with complete elimination observed at 30 mJ (both frequencies) and at 20 mJ/10 Hz. Inhibition zone diameters were largest at 30 mJ/10 Hz (8.6 ± 0.39 mm), while 2% CHX produced a slightly larger, but not statistically significant, inhibition zone (13 ± 2.9 mm vs. 11.5 ± 14.4 mm; P>.05). Both laser parameters and CHX significantly reduced S. mutans populations, demonstrating comparable antimicrobial efficacy at higher laser energies. Conclusion: High-energy 1064 nm Q-switched Nd:YAG laser therapy effectively reduces S. mutans counts in vitro, with results comparable to 2% CHX. Laser application may serve as an alternative or adjunctive strategy for microbial control in dental treatments, particularly in cases where chemical antiseptics are limited or contraindicated.